Comparative Genomics of Pandoraea, a Genus Enriched in Xenobiotic Biodegradation and Metabolism - Peeters, Charlotte; De Canck, Evelien; Cnockaert, Margo; De Brandt, Evie; Snauwaert, Cindy; Verheyde, Bart; Depoorter, Eliza; Spilker, Theodore; LiPuma, John J.; Vandamme, Peter (Frontiers in Microbiology, 2019)
Comparative analysis of partial gyrB, recA and gltB gene sequences of 84 Pandoraea reference strains and field isolates revealed several clusters that included no taxonomic reference strains. The gyrB, recA and gltB phylogenetic trees were used to select 27 strains for whole genome sequence analysis and for a comparative genomics study that also included 41 publicly available Pandoraea genome sequences. The phylogenomic analyses included a Genome BLAST Distance Phylogeny approach to calculate pairwise digital DNA–DNA hybridization values and their confidence intervals, average nucleotide identity analyses using the OrthoANIu algorithm, and a whole-genome phylogeny reconstruction based on 107 single-copy core genes using bcgTree. These analyses, along with subsequent chemotaxonomic and traditional phenotypic analyses, revealed the presence of 17 novel Pandoraea species among the strains analyzed, and allowed the identification of several unclassified Pandoraea strains reported in the literature. The genus Pandoraea has an open pan genome that includes many orthogroups in the ‘Xenobiotics biodegradation and metabolism’ KEGG pathway, which likely explains the enrichment of these species in polluted soils and participation in the biodegradation of complex organic substances. We propose to formally classify the 17 novel Pandoraea species as P. anapnoica sp. nov. (type strain LMG 31117T=CCUG 73385T), P. anhela sp. nov. (type strain LMG 31108T=CCUG 73386T), P. aquatica sp. nov. (type strain LMG 31011T=CCUG 73384T), P. bronchicola sp. nov. (type strain LMG 20603T=ATCC BAA-110T), P. capi sp. nov. (type strain LMG 20602T=ATCC BAA-109T), P. captiosa sp. nov. (type strain LMG 31118T=CCUG 73387T), P. cepalis sp. nov. (type strain LMG 31106T=CCUG 39680T), P. commovens sp. nov. (type strain LMG 31010T=CCUG 73378T), P. communis sp. nov. (type strain LMG 31110T=CCUG 73383T), P. eparura sp. nov. (type strain LMG 31012T=CCUG 73380T), P. horticolens sp. nov. (type strain LMG 31112T=CCUG 73379T), P. iniqua sp. nov. (type strain LMG 31009T=CCUG 73377T), P. morbifera sp. nov. (type strain LMG 31116T=CCUG 73389T), P. nosoerga sp. nov. (type strain LMG 31109T=CCUG 73390T), P. pneumonica sp. nov. (type strain LMG 31114T=CCUG 73388T), P. soli sp. nov. (type strain LMG 31014T=CCUG 73382T) and P. terrigena sp. nov. (type strain LMG 31013T=CCUG 73381T).